La dynamique des représentations dans les contacts interculturels - Yanaprasart, Patchareerat (My University, 2002)
This study presents a meeting point between hidden thought and direct speech, linking anthropology to linguistics. The discursive processing of the social dimension of representations is our study object. Starting from discursive clues to be used as linguistic tools, the study of social categorization provides us with an access route to the reflexion that each enunciator has restructured from his ideas and the position he held, in comparison with what he had experienced in the communication among heterogeneous groups living in the same society. Within the context of this work1, we asked French and Thai partners to describe their meetings with the intention of obtaining the phenomena of positioning and explication of representations as well as the evolution of social images, the modification of stereotypes and the ever-changing nature of representations of the "Other" following contacts. Their representations of intercultural contact are thus built on a personal real life-experience.